Information Seeking and Usage Behavior of @rlthingy’s Twitter Followers for Satisfying Their Information Needs - Diah Kurnia Hidayati (Universitas Ahmad Dahlan, 2021)
Social media became an information source. That situation made people rely more upon their information needs from social media despite its credibility. Its users also used Twitter to seek information, which is increasingly becoming more popular with a Twitter feature called Mention Confess (Menfess), developed by the Twitter account @biolbe. A Twitter account that provided Mention Confess services with the most followers in Indonesia is @rlthingy. @rlthingy aimed to satisfy the information needs of its followers' personal lives. Information Seeking Theory with qualitative methods and Netnography research design used in this research. This study showed the follower's interaction in seeking and using the information on @rlthingy's Twitter account.The results showed many personal motivations that made followers do the information-seeking on @rlthingy. Those were like the anonymous feature offered, comprehending people's opinions on a problem to add insight and provide entertainment. The anonymous feature was viral for @rlthingy's followers because they could ask questions without thinking about the stereotypes that would attach to them. The study also showed how followers would always be synergistic about seeking and using information simultaneously. That situation happened because they felt responsible for the information and co-existence with other followers' problems. Information behavior made by @rlthingy followers also made by liking Mention Confess, which were considered necessary. The results also showed information processing behavior done. Information procession depended on the nature of the Public Significance of the urgency of information. If the answer had a high Public Significance and being in an urgent situation for @rlthingy followers, they would immediately believe in the information and vice versa.